Analysis of attitudes of local communities towards the creation of protected areas on the example of national parks in Austria and Germany - Szalast-Piwińska, Małgorzata (Polish Journal of Agronomy, 2023)
The aim of this study was to present the attitudes of localcommunities in the process of creating a national park – a preciousnatural area with a high protection regime. The study takesinto account the actions of the authorities and legal regulationsconcerning, among other things, the possibility of agriculturaland economic activities in the park.The considerations were based on the presentation of thecases of the establishment of the Nationalpark Donau-Auen inAustria and the Nationalpark Schwarzwald in Germany. Amongothers, official documents, publications, reports, studies, onlineinformation (e.g. on websites) and legal acts concerning natureconservation and national parks were analysed.The factor that mobilised communities in the process of establishingthe two national parks was the decisions of the publicauthorities. The Donau-Auen Nationalpark is an example of effectivecommunity action in defence of nature. Its creation waspreceded, among other things, by the ‘Hainburg Aubsetz’ campaign,a community initiative demonstrating the importance ofnature conservation in Austria. The creation of the SchwarzwaldNationalpark, on the other hand, is an example of the NIMBY(not in my back yard) phenomenon, where the local communityaccepts nature conservation but opposes it when its rights are curtailed.The dialogue between the authorities and the public hasshown in both cases that awareness-raising activities on decisionsrelated to the creation of a protected area are necessary. The approvalof local communities in the creation of protected areas islinked to the expectation that these areas will provide social andeconomic benefits. The creation of a protected area can meanprofits for businesses in the area or a worsening of the living situationof landowners excluded from production, indicating a linkbetween nature conservation and living standards and poverty. Inthe cases discussed, there is no data on the level of poverty andits impact on the attitudes of local communities towards protectedareas. It seems important to carry out relevant research in thisregard in the future.